ラットにおける対処不能電撃の経験が後の食餌性弁別学習に及ぼす効果 - 園田, 明人 (The Japanese Journal of Psychonomic Science, 1990)
Thirty male Wistar rats, which were previously trained in a Skinner box with left and right lever press, were administered one of three conditions: escapable, yoked inescapable, and no shocks. Twenty-four hours after the treatment, the rats were tested in a Skinner box on the appetitive left-right single alternation discrimination task between two levers. Results showed that the rats pretreated with inescapable shock responded significantly less during an initial stage of the task than the subjects with escapable shock and the no shock controls; motivational deficit was found in the inescapable group. In a later stage, however, the rate of correct response in the inescapable group was significantly lower than those in the other groups despite no significant difference in the number of responses was found among the groups. The results indicates that exposure to uncontrollability produced associative deficits; associative retardation is the main factor of the effects of uncontrollable shock. The generality of associative factors in the learned helplessness effects is discussed in relation to other studies which employed different types of learning task.